CREATIVE CONTRIBUTION OF KARABAKH WRITERS TO THE ACTIVITY OF THE MALLA NEDREDIN JOURNAL - Vasif, K.G (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
Since the publication of "Molla Nasreddin" journal led Jalil Mammadguluzadeh therein steel cooperate Mirza Alekper Bardhan, Gurbanali Sharifzadeh, Omar Faig Nemanzadeh, Mamed Said Ordubadi, Aligulu Gemkgusar, Mammadali Sidgi, Salman Mumtaz, Ali Razi Shamchizade, Mirza Mohammed Ahundov and other progressive intellectuals, popular and prominent figures in Russian realistic literature, the democratic press. Soon, these far-sighted advanced writers formed the literary school "Molla Nasreddin" and this school turned into a new stage in the history of the development of social, political, artistic and aesthetic thought. Some poets and writers who held a special place in the literary and artistic world of that era and had similar public positions with "Molla Nasreddin", welcomed the appearance of such a journal, appeared in the periodical press and expressed political thoughts and reviews about the publication, the editor Jalil Mamedkulizade and his works. In the publication of the journal and the creation of the literary school of the same name, a significant role belonged to the Karabakhian friends and colleagues of the writer. During the period of rampant reaction in 1907-1908, newspapers were prosecuted, they were closed one after the other. Both the editorial staff of "Molla Nasreddin" and the printing house are searched, harass the editor and employees, and hostile attacks are carried out under the cover of criticism. Together with the progressive figures of that era, U. Hajibeyov, other writers defended the magazine in print from anger and persecution of the reactionary regime, called for preserving the purity of the pen, writing sharply, but artistically, boldly, juicy, even courteously ironic.